PSV-11 Accuracies of genomic prediction for reproductive traits in PRRSV-infected sows. (30th November 2020) - Hickmann, Felipe; Neto, José Braccini; Kramer, Luke; Gray, Kent; Huang, Yijian; Dekkers, Jack; Sanglard, Letícia P; Serão, Nick
Abstract: Recent studies on host-genetics of response to porcine reproductive and respiratory syndrome virus (PRRSV) infection have shown that genetic markers can be used to predict performance in growing pigs. On the other hand, no work has been done on the genomic prediction of reproductive performance in PRRSV-infected sows. Thus, the objective of this work was to assess the accuracies of genomic prediction for reproductive traits in PRRSV-infected sows. A total of 475 Duroc and 405 Landrace sows with 30K SNP genotypes had farrowing performance data during the outbreak on: number of piglets born alive (NBA), stillborn piglets (NSB), mummified piglets (NM), piglets born dead (NBD; NSB+NM), total number of piglets born (TNB; NBA+NBD), and piglets weaned (NW). Genomic prediction was performed by Bayes-B with a model fitting parity as fixed-effect and SNP effects as random. Analyses were performed for two scenarios: within-breed and between-breed. For the within-breed prediction, 4-fold cross-validation was used. For the between-breed prediction, all data for each breed were used. Accuracy of genomic prediction (AGP) was calculated as the correlation between genomic estimated breeding values and pre-adjusted phenotype, divided by square-root of heritability. For the within-breed prediction, AGP (± standard deviation) for NBA, NBD, NM, NSB, NW, and TNB were 0.24±0.05, 0.07±0.10, -0.27±0.06, -0.24±0.09, -0.05±0.05, 0.19±0.03, respectively, for Duroc, and 0.37±0.02, 0.38±0.11, 0.30±0.07, 0.60±0.10, 0.09±0.11, 0.15±0.10, respectively, for Landrace. For the between-breed prediction, AGP for NBA, NBD, NM, NSB, NW, and TB were 0.28, -0.17, -0.01, 0.37, 0.27, and 0.29, respectively, when training on Landrace and validating on Duroc, and 0.28, -0.14, 0.01, 0.15, 0.23, and -0.01, respectively, when training on Duroc and validating on Landrace. Results show that the accuracies of genomic prediction for reproductive traits during a PRRSV outbreak are low to moderate.